Profil Hematologi dan Pertambahan Bobot Badan Harian Ayam Broiler yang Diberi Cekaman Panas pada Suhu Kandang yang Berbeda - Sugito Sugito (Jurnal Agripet, 2009)
The profile of hematology and broiler daily body weight gain which treated with heat stress at different cage temperatureABSTRACT. A research have been conducted to find the impact of heat stress at 3 level of cage temperature on hematology profile and broiler daily body weight gain. Sixteen broilers (strain Cobb) at the age of 20 days were randomly divided to 4 groups. First group was control group that treated without given heat stress (KL). Second, third, and fourth groups were treated with heat stress in cages with temperature, respectively 33 1oC, 36 1oC, and 39 1oC. Heat stress was given 4 hours daily during 7 days consecutively. The result indicated that cage temperature up to 36 1oC has not significantly affected hematology profile and broiler daily body weight gain. The impact of increasing temperature have been found at cage temperature of 39 1oC after 7 days of treatment, which were the increasing number of leucocytes, decreasing number of erythrocytes, and decreasing of broiler daily body weight gain. The broiler of the age above 20 to 27 days that exposed heat stress during 4 hour per day in the cage temperature of 39 1oC can obtain heat stress in serious level.